A study on the effect of fitting rooms on consumer behavior "does the fitting room affect the decision of a consumer whether to buy the clothes or not? - Sia, Ana Marie Moreno; Mayo, Adelaida Villaraza (1995.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Consumer behavior -- Philippines